Investigation of the Household Waste Generation and Wastewater Management Techniques in Bogra Municipal Area (Journal of Environmental Science and Natural Resources, 2016)
The study was conducted to investigate the household waste generation and wastewater management phenomena in the Bogra municipal area during the period from October 2014 to April 2015, One hundred respondents from 7 wards of Bogra municipality were interviewed to carry out the study. The study investigated that the awareness level of the respondents increases with higher education and they indicated the crude disposal of municipal solid waste as the source of health hazards and environmental pollution. Result of the study showed that pH was slightly acidic, the concentration of sodium (Na) and sulfur (S) exceeded than desired level where nitrogen (N) and phosphorus (P) were within the effluent standard limit set by DoE. As the quality of wastewater was not satisfactory, it is necessary to explore possible treatment requirements before discharge to the natural stream. Bogra municipal authority should improve municipal waste collection and disposal system to maintain sound environment of the area. Various NGOs and local clubs should also take steps to keep the environment clean.J. Environ. Sci. & Natural Resources, 9(1): 123-126 2016